Q. 5 B5.0( 2 Votes )

# <span lang="EN-US

Sum of n terms of AP is given as:

Sum of p terms, Sp is given as:

Sum of q terms, Sq is given as:

Now, its given that Sp = Sq

2ap + pd(p - 1) = 2aq + qd(q - 1)

2a(p - q) + d(p2 - q2) = (p - q)d

2a(p - q) + d(p - q)(p + q) = (p - q)d

2a + d(p + q) = d

2a = - d(p + q - 1) ……………..(1)

Sum of (p + q) terms :

Sp + q =

From eq(1) putting value of 2a,

Sp + q =

Sp + q = 0.

Hence proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any five Maharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any four Maharashtra Board - Algebra Papers

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1

<span lang="EN-USMHB - Mathematics Part-1